KAJIAN ALTERNATIF PENANGGULANGAN BANJIR (STUDI KASUS SUNGAI LADAPA DI KABUPATEN GORONTALO) - Sarminingsih, Anik (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Flood  mitigation  is  a  part  of  water  resources  management  widely  with  scope  are  consist of conservation, controlled and water used. The concept of water controlled is called Flood Control or Flood Mitigation/Flood Damage Mitigation. There are two kinds of flood control, structural and non structural effort. Structural effort is an effort which tends to engineering technique which is aimed to modification the flood discharge and the stage of flood damage. Flood discharge (Q, m3/sec) is the function of velocity (V, m/sec) and cross section area of the river/channel (A, m2). Efforts  of  flood  control  can be  carried  out by  justified  of  the  third  components.  Non-structural  effort  is  aimed  to  avoid  and  press  the problem  that  caused by  flood  with  some  activities  like arrangement  of  flood  plain  and  watershed development.    Non-structural    effort  usually  is conducted  for  long  period  goal.  Therefore  carrying this  effort  need  consistency  all  of stakeholder.  Participatory  approach  from  stakeholder  is  the  key of  success  of  non  structural effort.